Applied anatomy and surgical technique of the lateral single‐position L5–S1 fusion. Issue 5 (5th May 2021) - Bodon, Gergely; Kiraly, Kristof; Baksa, Gabor; Barany, Laszlo; Kiss, Mate; Hirt, Bernhard; Pussert, Arndt; Timothy, Jake; Stubbs, Lenny; Khajavi, Kaveh; Braly, Brett
Abstract: The latest development in the anterior lumbar interbody fusion (ALIF) procedure is its application in the lateral position to allow for simultaneous posterior percutaneous screw placement. The technical details of the lateral ALIF technique have not yet been described. To describe the surgical anatomy relevant to the lateral ALIF approach we performed a comprehensive anatomical study. In addition, the preoperative imaging, patient positioning, planning of the skin incision, positioning of the C‐arm, surgical approach, and surgical technique are discussed in detail. The technique described led to the successful use of the lateral ALIF technique in our clinical cases. No lateral ALIF procedure needed to be aborted during these cases. Our present work gives detailed anatomical background and technical details for the lateral ALIF approach. This teaching article can provide readers with sufficient technical and anatomical knowledge to assist them in performing their first lateral ALIF procedure.